Analyzing the reason for students' lack of interest in learning arts and culture as subjects in Class IV C at SDN 210 Babakan Sinyar - Nasihah, Farah Lutfiah; Istiqomah, Riski Alita; Wiyanto, Yuli Tri (PT. Riset Press International, 2024)
The study entitled